Aqueous zinc ion battery positive electrode material, preparation method thereof, positive plate and battery
By using composite material strategy and ion doping in the positive electrode material of aqueous zinc ion battery, a positive electrode material with carbon coating and chromium doping was prepared, which solved the problems of unstable structure and insufficient specific capacity of the existing positive electrode material, and achieved the Improvement of high specific capacity and good electrochemical performance.
Patent Information
- Application Number
- CN202411618135.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing positive electrode materials of zinc ion batteries in water system have problems such as unstable structure, insufficient specific capacity and poor conductivity, which limits the commercial application of batteries.
Through composite material strategy and ion doping, a positive electrode material of aqueous zinc ion battery with carbon coated and chromium doped was prepared. Cr3+ was pre-embedded into VO2 by hydrothermal method to form sea urchin-like CrVO, and the structure was enhanced by carbon coating. stability.
The structural stability, high specific capacity, good reversibility and rate performance of the positive electrode material are achieved, and the electrochemical performance of the aqueous zinc ion battery is significantly improved.
Smart Images

Figure CN119495726A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of aqueous zinc ion batteries, and more specifically, relates to an aqueous zinc ion battery positive electrode material and a preparation method thereof, a positive electrode sheet and a battery. Background Art
[0002] As an electrochemical energy storage device with high energy density, high efficiency, convenience and strong flexibility, lithium-ion batteries (LIBs) have been widely used in electronic products and large-scale grid energy storage in the past few decades. However, LIBs have problems such as insufficient electrolyte safety and scarce lithium resources, which are difficult to be effectively solved. Aqueous zinc-ion batteries (AZIBs) are widely used due to the high safety of the aqueous electrolyte they use and the high theoretical capacity of metallic zinc (820mAh g -1 / 5854mAh cm -3 ) and other advantages, and has attracted widespread attention. However, the limitation of cathode materials of aqueous zinc-ion batteries (AZIBs) is one of the main reasons hindering the commercialization of aqueous zinc-ion batteries.
[0003] Nowadays, manganese-based compounds, Prussian blue analogs and vanadium-based compounds have been widely studied as positive electrodes for aqueous zinc-ion batteries. However, although manganese-based compounds have ultra-high specific capacity as positive electrodes, they will experience severe structural collapse during the zinc ion insertion / extraction process, resulting in capacity decay. Although Prussian blue analogs have a stable framework structure, their capacity is too low compared to manganese-based compounds and vanadium-based compounds.
[0004] Due to its amazing capacity and abundant natural reserves, vanadium-based compounds have attracted widespread interest among scientists as positive electrodes for aqueous zinc-ion batteries. So far, scientists have conducted a lot of research on vanadium-based compounds, revealing the application prospects of vanadium-based compounds as positive electrodes for aqueous zinc-ion batteries and promoting the application of vanadium-based materials as positive electrodes for aqueous zinc-ion batteries. Among them, the unique tunnel-like structure of vanadium dioxide is conducive to the reversible insertion / extraction of zinc ions, but the instability of the structure and poor conductivity of vanadium dioxide hinder its widespread application.
[0005] Therefore, it is urgent to propose a new aqueous zinc ion battery positive electrode material and a preparation method thereof, an aqueous zinc ion battery positive electrode sheet and an aqueous zinc ion battery. Summary of the invention
[0006] The purpose of the present invention is to address the deficiencies of the prior art and to provide an aqueous zinc ion battery positive electrode material and a preparation method thereof, a positive electrode sheet and a battery. The aqueous zinc ion battery positive electrode material of the present invention has a stable structure, high specific capacity, good reversibility and excellent rate performance.
[0007] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a positive electrode material for an aqueous zinc ion battery, the preparation method comprising the following steps:
[0008] S1: mixing an oxalic acid aqueous solution and a CrNO3 aqueous solution to obtain a first mixed solution;
[0009] S2: mixing the first mixed solution with V2O5 and superconducting carbon, stirring and ultrasonically treating to obtain a second mixed solution, and subjecting the mixture to a hydrothermal reaction to obtain a reaction product;
[0010] S3: sequentially cooling, centrifugally washing and vacuum freeze-drying the reaction product to obtain the aqueous zinc ion battery positive electrode material.
[0011] According to the present invention, preferably, in step S1:
[0012] The mixing ratio of oxalic acid to water in the oxalic acid aqueous solution is (0.8-1.2): (55-65) g / mL;
[0013] The mixing ratio of CrNO3·9H2O and water in the CrNO3 aqueous solution is (6-45): (950-1050) g / mL;
[0014] The volume ratio of the oxalic acid aqueous solution to the CrNO3 aqueous solution is (2.5-3.5):(0.8-1.2).
[0015] According to the present invention, preferably, in step S2:
[0016] The mass ratio of V2O5, CrNO3·9H2O and superconducting carbon is (5-40):(6-18):(0.5-4);
[0017] The mixing temperature is 18-30°C, and the mixing time is 2.5-3.5h;
[0018] The ultrasonic treatment time is 1-2h;
[0019] The temperature of the hydrothermal reaction is 150-200° C. and the time is 24-26 hours.
[0020] In the present invention, the equipment used for the hydrothermal reaction is a 50 mL polytetrafluoroethylene-lined reactor.
[0021] According to the present invention, preferably, in step S3, the vacuum freeze-drying treatment time is 8-10 hours.
[0022] In the present invention, the washing liquid used in the centrifugal washing is water and ethanol.
[0023] The second aspect of the present invention provides an aqueous zinc ion battery positive electrode material prepared by the method for preparing the aqueous zinc ion battery positive electrode material.
[0024] The third aspect of the present invention provides a positive electrode sheet for an aqueous zinc ion battery, wherein the positive electrode sheet is prepared by uniformly mixing a positive electrode active material, a conductive agent and a binder solution to form a slurry, coating the slurry on a current collector, and drying the slurry.
[0025] The positive electrode active material is the above-mentioned aqueous zinc ion battery positive electrode material.
[0026] According to the present invention, preferably, the mass ratio of the positive electrode active material, the conductive agent and the binder solution is (6.5-7.5): (1.5-2.5): (0.5-1.5).
[0027] According to the present invention, preferably, the conductive agent is at least one of SuperP, acetylene black, VGCF, carbon nanotubes, carbon nanofibers, graphene and graphite.
[0028] According to the present invention, preferably, the mass concentration of the binder in the binder solution is 4%-10%, the binder is PVDF, and the solvent in the binder solution is N-methylpyrrolidone.
[0029] According to the present invention, preferably, the current collector is a titanium foil with a thickness of 15-25 μm.
[0030] According to the present invention, preferably, the drying treatment is carried out at a temperature of 70-100° C. and for a time of 8-10 h.
[0031] A fourth aspect of the present invention provides an aqueous zinc ion battery, wherein the positive electrode sheet of the battery is the positive electrode sheet described above.
[0032] According to the present invention, preferably, the negative electrode sheet of the battery is a pure zinc sheet.
[0033] According to the present invention, preferably, the electrolyte of the battery is an aqueous solution of zinc trifluoromethanesulfonate with a concentration of 2.5-3.5 mol / L.
[0034] The beneficial effects of the technical solution of the present invention are as follows:
[0035] The present invention uses composite material strategy and ion doping to make the prepared aqueous zinc ion battery positive electrode material have a stable structure, high specific capacity, good reversibility and excellent rate performance. Specifically:
[0036] In the present invention, Cr 3+ Ions due to their unique 3D 3The electronic configuration can reduce the delocalization of electrons. In addition, the different oxidation states of Cr and V are beneficial to improve their electronic conductivity by adjusting the electronic structure. -1 ), which is more conducive to stabilizing the framework structure of the host material, thereby improving the cycle stability of the VO2 positive electrode. Based on this, the present invention uses a hydrothermal method to make Cr 3+ Sea urchin-shaped CrVO is obtained by pre-embedding VO2. Cr as a pillar 3+ It can stabilize the matrix structure, improve the conductivity, and prevent the embedded Zn 2+ In addition, in order to further increase the structural stability of the material, the present invention synthesizes carbon-coated CrVO@C as the positive electrode material of the rechargeable aqueous zinc ion battery by hydrothermal method, so that the positive electrode material of the present invention has good electrochemical stability. The present invention is of great significance for the research on the composite material doped with the positive electrode of the aqueous zinc ion battery.
[0037] The present invention obtains a carbon-coated and chromium-doped aqueous zinc ion battery positive electrode material through a hydrothermal reaction. The aqueous zinc ion battery positive electrode material of the present invention increases the interlayer spacing through the intercalation of chromium ions, and the carbon coating makes the structure more compact, which is conducive to the insertion and extraction of zinc ions and has a more stable structure.
[0038] The aqueous zinc ion battery positive electrode material of the present invention exhibits high specific capacity, excellent cycle performance and rate performance in aqueous zinc ion batteries. -1 At a current density of 2.5 MW, there is still 284 mAh g after 50 cycles. -1 Specific capacity, at 3A g -1 After 500 cycles at the same current density, the specific capacity is 192 mAh g -1 In addition, the aqueous zinc ion battery positive electrode material of the present invention has excellent rate performance, and the capacity retention rate after cycling is 92%.
[0039] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention with reference to the accompanying drawings.
[0041] Figure 1 The X-ray diffraction pattern of an aqueous zinc ion battery positive electrode material prepared by a method for preparing an aqueous zinc ion battery positive electrode material provided in Example 1 of the present invention is shown (Intensity is the diffraction intensity, 2θ (degree) is the angle, and "PDF#82-2392" is the standard card number).
[0042] Figure 2 The Raman spectrum of an aqueous zinc ion battery positive electrode material prepared by a method for preparing an aqueous zinc ion battery positive electrode material provided in Example 1 of the present invention is shown (Intensity is the Raman spectrum intensity, and Raman Shift is the Raman shift).
[0043] Figure 3 The small current cycle performance diagram (Specific Capasity, Cycle number, Coulombic Efficiency) of the aqueous zinc ion battery provided in Example 1 of the present invention is shown.
[0044] Figure 4 The high current cycle performance diagram of the aqueous zinc ion battery provided in Example 1 of the present invention is shown.
[0045] Figure 5 The performance comparison diagram of the aqueous zinc ion battery provided in Example 1 of the present invention is shown (comparison between the aqueous zinc ion battery positive electrode material prepared in Example 1 and vanadium dioxide and CrVO).
[0046] Figure 6 The figure shows the rate performance of the aqueous zinc ion battery provided in Example 1 of the present invention.
[0047] Figure 7 The small current cycle performance diagram of the aqueous zinc ion battery provided in Example 2 of the present invention is shown.
[0048] Figure 8 The figure shows the rate performance of the aqueous zinc ion battery provided in Example 2 of the present invention.
[0049] Fig. 9 The high current cycle performance diagram of the aqueous zinc ion battery provided in Example 3 of the present invention is shown. DETAILED DESCRIPTION
[0050] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0051] Example 1
[0052] This embodiment provides a method for preparing a positive electrode material for an aqueous zinc ion battery, the preparation method comprising the following steps:
[0053] S1: oxalic acid and deionized water are mixed in a ratio of 1:60 g / mL, and stirred evenly to obtain an oxalic acid aqueous solution; CrNO3·9H2O and deionized water are mixed in a ratio of 8:1000 g / mL, and stirred evenly to obtain a CrNO3 aqueous solution; the oxalic acid aqueous solution and the CrNO3 aqueous solution are mixed in a volume ratio of 3:1 to obtain a first mixed solution;
[0054] S2: Mix the first mixed solution with V2O5 and superconducting carbon at 25°C for 3 hours and perform ultrasonic treatment for 1.5 hours to obtain a second mixed solution; put the second mixed solution into a 50ml polytetrafluoroethylene-lined reactor, and perform hydrothermal reaction at 180°C for 24 hours to obtain a reaction product (suspension);
[0055] Among them, the mass ratio of V2O5, CrNO3·9H2O and superconducting carbon is 35:8:3;
[0056] S3: The reaction product (suspension) was cooled to room temperature, poured into a centrifuge tube, and washed 6 times by alternating centrifugation with deionized water and alcohol; the washed solid was placed in a vacuum freeze dryer and dried for 8 hours to obtain a carbon-coated and chromium-doped aqueous zinc ion battery positive electrode material (CrVO@C), such as Figure 1 , 2 shown.
[0057] This embodiment also provides a positive electrode sheet for an aqueous zinc ion battery, wherein the positive electrode sheet is prepared by uniformly mixing a positive electrode active material, a conductive agent and a binder solution to form a slurry, coating the slurry on a 20 μm titanium foil (a disc with a radius of 7 mm), and drying the slurry at 70° C. for 8 h.
[0058] The positive electrode active material is the aqueous zinc ion battery positive electrode material described in this embodiment;
[0059] The conductive agent is acetylene black;
[0060] The mass concentration of the binder in the binder solution is 6%, the binder is PVDF (polytetrafluoroethylene), and the solvent in the binder solution is N-methylpyrrolidone
[0061] The mass ratio of the positive electrode active material, the conductive agent and the binder solution is 7:2:1;
[0062] This embodiment also provides an aqueous zinc ion battery, wherein the positive electrode sheet of the battery is the positive electrode sheet described in this embodiment;
[0063] The negative electrode sheet of the battery is a zinc sheet with a thickness of 200 μm. After being polished to remove the oxide layer, it is placed in a beaker and ultrasonically washed with ethanol for 30 minutes and dried to obtain;
[0064] The electrolyte of the battery is a 3 mol / L zinc trifluoromethanesulfonate aqueous solution.
[0065] The preparation of the battery comprises: placing a steel mesh and a negative electrode sheet into a CR 2016 button battery shell, covering it with a glass fiber diaphragm, dripping 90-100 microliters of electrolyte on the diaphragm, then installing a positive electrode sheet and a steel mesh, and finally sealing the battery to obtain a rechargeable aqueous zinc ion battery.
[0066] The electrochemical performance of the aqueous zinc ion battery of this embodiment was tested. The charge and discharge cut-off voltage during the test was 0.2V-1.3V (vs. Zn 2+ / Zn), the results are as follows:
[0067] like Figure 3 As shown, the aqueous zinc ion battery prepared in this embodiment has a current density of 0.1Ag -1 After 50 cycles, there is still 284 mAh g -1 The reversible specific capacity;
[0068] like Figure 4 As shown in the figure, the aqueous zinc ion battery prepared in this example has a current density of 3A g -1 After 500 cycles, the specific capacity is 192 mAh g -1 .
[0069] like Figure 6 As shown in the figure, it is the rate performance diagram of the aqueous zinc ion battery prepared in this embodiment. The positive electrode material of the aqueous zinc ion battery prepared in this embodiment has a stable specific capacity contribution at different current densities. -1 The current densities under these conditions were 348, 295, 279, 254, 230, and 156 mAh g -1 Specific capacity, showing good rate performance.
[0070] Example 2
[0071] The difference between this embodiment and embodiment 1 is only that:
[0072] The mixing ratio of CrNO3·9H2O and water in the CrNO3 aqueous solution is 16:1000 g / mL;
[0073] The mass ratio of V2O5, CrNO3·9H2O and superconducting carbon is 35:16:3;
[0074] The electrochemical performance of the aqueous zinc ion battery of this embodiment was tested. The charge and discharge cut-off voltage during the test was 0.2V-1.3V (vs. Zn 2+ / Zn), the results are as follows:
[0075] like Figure 7 As shown, the aqueous zinc ion battery prepared in this embodiment has a current density of 0.1Ag -1 After 50 cycles, there is still 238 mAh g -1 The reversible specific capacity;
[0076] like Figure 8 As shown in the figure, it is the rate performance diagram of the aqueous zinc ion battery prepared in this embodiment. The positive electrode material of the aqueous zinc ion battery prepared in this embodiment has a stable specific capacity contribution at different current densities. -1 The current densities under these conditions were 261, 231, 210, 194, 174, and 107 mAh g -1 Specific capacity, showing good rate performance.
[0077] Example 3
[0078] The difference between this embodiment and embodiment 1 is only that:
[0079] The mixing ratio of CrNO3·9H2O and water in the CrNO3 aqueous solution is 40:1000 g / mL;
[0080] The mass ratio of V2O5, CrNO3·9H2O and superconducting carbon is 7:8:1;
[0081] The electrochemical performance of the aqueous zinc ion battery of this embodiment was tested. The charge and discharge cut-off voltage during the test was 0.2V-1.3V (vs. Zn 2+ / Zn), the results are as follows:
[0082] like Fig. 9 As shown in the figure, the aqueous zinc ion battery prepared in this example has a current density of 3A g -1 After 500 cycles, the specific capacity is 91 mAh g -1 .
[0083] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A method for preparing a positive electrode material for an aqueous zinc ion battery, characterized in that: The preparation method comprises the following steps: S1: mixing an oxalic acid aqueous solution and a CrNO3 aqueous solution to obtain a first mixed solution; S2: mixing the first mixed solution with V2O5 and superconducting carbon, stirring and ultrasonically treating to obtain a second mixed solution, and subjecting the mixture to a hydrothermal reaction to obtain a reaction product; S3: sequentially cooling, centrifugally washing and vacuum freeze-drying the reaction product to obtain the aqueous zinc ion battery positive electrode material.
2. The method for preparing an aqueous zinc ion battery cathode material according to claim 1, wherein In step S1: The mixing ratio of oxalic acid to water in the oxalic acid aqueous solution is (0.8-1.2): (55-65) g / mL; The mixing ratio of CrNO3·9H2O and water in the CrNO3 aqueous solution is (6-45): (950-1050) g / mL; The volume ratio of the oxalic acid aqueous solution to the CrNO3 aqueous solution is (2.5-3.5):(0.8-1.2).
3. The method for preparing the positive electrode material for aqueous zinc ion batteries according to claim 1, wherein In step S2: The mass ratio of V2O5, CrNO3·9H2O and superconducting carbon is (5-40):(6-18):(0.5-4); The mixing temperature is 18-30°C, and the mixing time is 2.5-3.5h; The ultrasonic treatment time is 1-2h; The temperature of the hydrothermal reaction is 150-200° C. and the time is 24-26 hours.
4. The method for preparing an aqueous zinc ion battery cathode material according to claim 1, wherein In step S3, the vacuum freeze-drying treatment time is 8-10 hours.
5. The aqueous zinc ion battery positive electrode material prepared by the method for preparing the aqueous zinc ion battery positive electrode material according to any one of claims 1 to 4.
6. A positive electrode sheet for an aqueous zinc ion battery, characterized in that: The positive electrode sheet is prepared by uniformly mixing a positive electrode active material, a conductive agent and a binder solution to form a slurry, coating the slurry on a current collector, and drying the slurry. The positive electrode active material is the aqueous zinc ion battery positive electrode material as claimed in claim 5.
7. The aqueous zinc ion battery positive electrode sheet according to claim 6, wherein: The mass ratio of the positive electrode active material, the conductive agent and the binder solution is (6.5-7.5): (1.5-2.5): (0.5-1.5).
8. The aqueous zinc ion battery positive electrode sheet according to claim 6, wherein: The conductive agent is at least one of Super P, acetylene black, VGCF, carbon nanotubes, carbon nanofibers, graphene and graphite; The mass concentration of the binder in the binder solution is 4%-10%, the binder is PVDF, and the solvent in the binder solution is N-methylpyrrolidone; The current collector is a titanium foil with a thickness of 15-25 μm; The drying process is carried out at a temperature of 70-100° C. and for a time of 8-10 hours.
9. An aqueous zinc ion battery, characterized in that: The positive electrode sheet of the battery is the positive electrode sheet described in any one of claims 6 to 8.
10. The aqueous zinc ion battery according to claim 9, wherein: The negative electrode sheet of the battery is a pure zinc sheet; The electrolyte of the battery is an aqueous solution of zinc trifluoromethanesulfonate with a concentration of 2.5-3.5 mol / L.
Citation Information
Patent Citations
Nano Cr2V4O13 material as well as preparation method and application thereof
CN113277561A
Magnesium ion doped VO2 (B) material as well as preparation method and application thereof
CN116230925A
Oxygen-rich defect Cr0. 11V2O5. 16 nanobelt grown on stainless steel in situ and preparation method and application thereof
CN118062896A
Zinc ion battery vanadium-based positive electrode material, preparation method and application thereof
CN118373451A
Cited By
Composite positive electrode material and preparation method and application thereof
CN121149149A
Composite positive electrode material and preparation method and application thereof
CN121149149B